The Wife-Less Fathers in Shakespearean comedies are Insensitive Towards their Daughters and a Poor Judge of Men and Matters! The Impact of Absent Mothers on Father-Daughter Relationships in Shakespearean Comedies (Journal of Advances and Scholarly Researches in Allied Education, 2022)
William Shakespeare ( baptised 26th April 1564 – 23rd April 1616) is one of the finest men ofletters the world has ever produced whose worth and significance was felt not only by hiscontemporaries but also even till date across the globe and times. Though Shakespeare became amarried man at an early age of 18, his dramas majorly do not depict wives as strong characters or moreso the primary male characters do not have wives at all. Not to forget the fact that if the drama has astrong wife, like in Macbeth or Hamlet, the fate is doomed. On further analysis, we find that in quite a fewof his dramas, the father-daughter relationships are estranged chiefly because of the absence ofmothers literally or metaphorically. The present study focuses on discussing how the fathers areprimarily insensitive or indifferent to the needs of their daughters if their wives were not around. Toquote a few Leonato- Hero in Much Ado About Nothing, Shylock-Jessica in Merchant of Venice, andapparently Prospero- Miranda in The Tempest. The idea here is to establish a rationale about thesensitising effect of the mothers as wives and how imperative is their presence